THE EFECTIVENESS OF NUMBERED HEADS TOGETHER WITH GUIDED DISCOVERY LEARNING AND JIGSAW II WITH GUIDED DISCOVERY LEARNING VIEWED FROM ADVERSITY QUOTIENT - Qurrotul ‘Ain; Tri Atmojo Kusmayadi; Budi Usodo (Proceedings Education and Language International Conference, 2017)
This research was a quasi-experimental research with 2×3 factorial design aimed to find out the influence of learning model NHT with guided discovery learning and Jigsaw II with guided discovery learning for students’ mathematics achievement. The population of this study were all of the eleventh grade students of Junior High School in Karanganyar regency and sampling was done by stratified cluster random sampling. The data was collected by test, questionnaire, and documentation.The test of hypothesis used two-way analysis of variance with unequal cell, past analysis of variance with Scheffe’ method and significance level was 0.05. Based on hypothesis test, it could be concluded that (1) the learning model of Jigsaw II with guided discovery learning approach results students’ mathematics achivement better than NHT with guided discovery learning., (2) students’ mathematics achievement with the climbers type was as good as students’ mathematics achievement with the campers type, and students’ mathematics achievement with the campers type result better than students’ mathematics achievement the quitters type, (3) for each learning model, students’ mathematics achievement with the climbers type was as good as with students’mathematics achievement with the campers type, and students’ mathematics achievement the campers type result better than students’ mathematics achievement the quitters type, (4) for each category AQ, the learning model of Jigsaw II with guided discovery learning approach results better than students’ mathematics achivement learning model NHT with guided discovery learning.Keywords: Jigsaw II, Numbered Heads Together, Guided Discovery Learning, Adversity Quotient, Mathematics Achievement